Infant T‐cell acute lymphoblastic leukaemia with t(6;7) (TCRB‐MYB) translocation. (1st July 2021) - Ramdeny, Pemantah Sandheeah; Mullanfroze, Khushnuma; de Lorenzo, Paola; Grazia Valsecchi, Maria; Meijerink, Jules; Pieters, Rob; Baruchel, Andre; Vora, Ajay
Summary: T‐ALL is rare in infancy with only 10 (1.5%) of 651 patients of that subtype in the Interfant‐06 infant ALL trial. We report 3 cases of t(6;7) (TCR/MYB) infant T‐cell Acute Lymphoblastic Leukaemia who appear to have a distinct clinical presentation with CNS disease and refractory disease or late relapse.